Sequence and Effects of Glucocorticoid Receptor Nuclear Retention: An Aid to Understanding Nuclear Retention in Other Proteins? - Carrigan, Amanda (Université d'Ottawa / University of Ottawa, 2011)
Corticosteroid ligands activate the glucocorticoid receptor (GR). GR plays a role in glucose homeostasis, adipogenesis, inflammation, and mood and cognitive functions. Understanding the interplay of diverse forms of receptor regulation (including post-translational modification, cofactor interactions, ligand binding, and receptor localization) and their effects is important for understanding and developing more effective treatment for a variety of conditions. Prior to ligand binding, the naïve GR is primarily cytoplasmic, residing in a chaperone complex containing heat-shock proteins and immunophilins. Upon ligand-binding, alterations to the complex allow the receptor to dimerize and import into the nucleus. Nuclear GR interacts with transcriptional regulatory sequences and recruits cofactors to regulate specific gene expression. Upon hormone withdrawal, the original chaperone complex is reassembled and the receptor is exported to the cytoplasm. Interestingly, while the import of GR into the nucleus occurs very rapidly (t ½ = 5 min), the re-export is significantly slower (t ½ = 12-24h). Previous work by our lab and others has indicated the existence of a nuclear retention signal (NRS) within the GR. The NRS sequence of the GR, its interaction partners, and the role it might play in the activity of the receptor have not yet been fully defined. Work in the Hache lab indicates that mutation of the GR nuclear localization signal 1 (NL1) increases the export rate of nuclear GR to the cytoplasm, as well as compromising receptor import, suggesting that the NL1 overlapped an NRS sequence. In this work, I made a series of GR mutants, based on sequence from the SV40 large T antigen NLS, which lacks nuclear retention activity. Using these mutants, I found that GR nuclear retention is influenced by both specific residues within the hinge region and the location of the sequence within the receptor, as reintroduction of the NLS sequence at the N-terminus of the receptor retention mutant failed to reconstitute the retention activity. Agonist liganded and hormone-withdrawn receptor mutants showed a similar decrease in retention. By contrast, antagonist-withdrawn GR mutants were retained in the nucleus, possibly due to altered receptor configuration and interactions. Assays of GR-responsive promoter activation by receptor retention mutants showed that while no difference in the ability of retention mutants to activate transcription was seen at a simple promoter, activation of a complex promoter was compromised. This impaired transactivation for the SV506-523 mutant correlated with decreased histone H4 acetylation and PolII recruitment, while GR DNA-binding at the target promoter appeared to be unaffected. These results suggested that promoter-specific cofactor interactions might be implicated in GR nuclear retention. Loss of GR hinge interaction with Oct cofactors produced an incomplete loss of retention, suggesting overlapping signals, but not supporting Oct as a primary factor in GR retention. The overlap between important residues in GR nuclear retention and localization signals and the lack of retention shown by the SV40 NLS suggested that retention might be intrinsic to the sequence of particular NLS. Preliminary results suggest that the KT511-512 residues of GR may be of general importance in protein nuclear retention, while the role of proline is likely more variable. My research has focused on increasing our understanding of glucocorticoid receptor nuclear retention and its possible implications. I have determined that the KT511-512 residues of GR play an important role in its retention, and possibly also figure in nuclear retention of other proteins. These residues are involved in interactions which affect promoter-specific histone acetylation and transcriptional activation in GR, suggesting a reason for the existence of nuclear retention.
Keywords: glucocorticoid receptor; nuclear retention; steroid hormone receptor; export; NLS; trafficking